Effect of combined Japanese traditional medicines, keishibukuryogan and jidabokuippo, on postoperative soft tissue swelling in adult patients undergoing revascularization surgery for ischemic moyamoya disease: A comparison of two prospective cohort studies. Issue 1 (17th November 2022) - Ogasawara, Kuniaki; Kawamura, Tsuyoshi; Kobayashi, Masakazu; Akamatsu, Yosuke; Chida, Kohei; Fujiwara, Shunrou; Yoshida, Kenji; Koji, Takahiro; Kubo, Yoshitaka
Abstract: Aim: Indirect revascularization surgery for moyamoya disease (MMD) sometimes results in swelling of the soft tissues (including the temporalis muscle) compressing the cerebral hemispheres postoperatively. The present supplementary analysis of two prospective cohorts aimed to elucidate the effects of Japanese traditional medicines, keishibukuryogan and jidabokuippo, on postoperative soft tissue swelling in adult patients undergoing revascularization surgery for ischemic MMD. Methods: Thirty‐two patients treated using direct revascularization surgery alone without Japanese traditional medicine (the first original study) and another 22 patients treated using indirect revascularization surgery alone with perioperative administration of keishibukuryogan and jidabokuippo (the second original study) underwent computed tomography of the head before and 3 days after surgery. The postoperative swelling rate of soft tissues in the head ipsilateral to the surgery was calculated. Results: The postoperative swelling rate of the soft tissues was significantly lower in patients participating in the second original study (88.8 ± 31.6%) than in those participating in the first original study (127.1 ± 31.1%) ( p = 0.0002). When postoperative swelling rates of soft tissues in all 54 patients were arranged in descending order and divided into tertiles (186.7–132.0%, 130.0–92.4%, 92.3–44.3%), logistic regression analysis revealed that participation in the second original study was significantly associated with the bottom tertile of postoperative swelling rate of soft tissues (95% confidence interval, 4.90–100.12; p = 0.0098). Conclusion: Combined administration of Japanese traditional medicines, keishibukuryogan and jidabokuippo, can reduce postoperative soft tissue swelling in adult patients undergoing revascularization surgery for ischemic MMD.